Gold(I)-catalyzed diastereoselective hydroacylation of terminal alkynes with glyoxals - Shi, Shuai; Wang, Tao; Claus, Vanessa; Rudolph, Matthias; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2014)
The reaction of an α-ketoaldehyde and a terminal alkyne in the presence of piperidine and a catalytic amount of AuCl delivers 1,2-dicarbonyl-3-enes, products of the formal hydroacylation of the triple bond. The scope of the method is broad; different aryl substituents on the dicarbonyl unit and on the alkyne are well tolerated. The products can be transformed selectively into vinylquinoxalines. Mechanistic studies, including isotope-labeling experiments, indicate that after an initial A3-type conversion to propargylic amines, a subsequent base-mediated alkyne-to-allene isomerization and a hydrolysis of the enamine substructure during the workup deliver the formal hydroacylation products.